Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/sj.gene.6363946
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic analysis of interferon receptor polymorphisms in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a common inflammatory disease of the central nervous system characterized by progressive neurological dysfunction. No curative therapy is currently available, and approximately 80-90% of afflicted individuals are ultimately disabled. Interferon beta (IFNb) has been shown to decrease clinical relapses, reduce brain disease activity, and possibly slow progression of disability. However, the overall effect of treatment is partial and a substantial number of patients are considered poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 30 publications
(33 reference statements)
2
39
2
Order By: Relevance
“…This study, in which the Centre d'Esclerosi Mú ltiple de Catalunya was one of 4 collaborating centers, aimed to identify genes associated with response to interferon beta therapy and was performed among responder and nonresponder DNA pools using genotyping arrays (Affymetrix 100K). Although previously reported genetic associations [5][6][7][8][9][10][11] were not confirmed, the study identified candidate genes and underscored the genetic heterogeneity underlying response to interferon beta therapy in MS.…”
Section: Commentmentioning
confidence: 80%
“…This study, in which the Centre d'Esclerosi Mú ltiple de Catalunya was one of 4 collaborating centers, aimed to identify genes associated with response to interferon beta therapy and was performed among responder and nonresponder DNA pools using genotyping arrays (Affymetrix 100K). Although previously reported genetic associations [5][6][7][8][9][10][11] were not confirmed, the study identified candidate genes and underscored the genetic heterogeneity underlying response to interferon beta therapy in MS.…”
Section: Commentmentioning
confidence: 80%
“…Nevertheless, the frequency of relapses appears to be the least unreliable clinical predictor of a response to therapy but only for the year before treatment onset. Other non-clinical markers, such as those provided by non-conventional MRI, and especially pharmacogenetic markers could help to answer the question [30,31] .…”
Section: Resultsmentioning
confidence: 99%
“…89,116 The analysis of eight SNPs in the interferon receptor genes failed to show significant evidence of pharmacogenomic influences. 117 More recently, we applied advanced data-mining and predictive modeling tools to a longitudinal gene expression data set generated from MS patients treated with IFNb in order to discover higher-order predictive patterns associated with treatment outcome. 118 We identified nine sets of gene triplets whose expression, when tested before the initiation of therapy, can predict favorable response to with up to 87% accuracy.…”
Section: Genetic Variation and The Clinical Response To Therapy In Msmentioning
confidence: 99%